Diagnostic utility of GFAP and RANKL in thalassemia: Insights into neurological and bone-related alterations - F. M. Mohammed; Z. M. Qassam; W. S. Hassan; M. R. Lateef (Regulatory Mechanisms in Biosystems, 2025)
β-thalassemia a major health challenge in many parts of the world, including the Middle East. This study aimed to explore the diagnostic relevance of two biochemical markers ( GFAP and RANKL ) in thalassemia patients. This cross-sectional study was conducted from January to April 2024 at the International Center for Research and Development Laboratories. A total of 90 participants were enrolled, including 66 patients with confirmed β-thalassemia and 24 age- and sex-matched healthy controls. Eligibility criteria for patients included diagnosis based on hematological and genetic tests, age above 18, and absence of comorbidities. Individuals with acute infections, recent blood transfusions, or autoimmune/inflammatory diseases were excluded. Ve n ous blood was collected, and serum GFAP and RANKL levels were measured using ELISA kits (Elabscience, China). Data were analyzed in SPSS v25 using independent t-tests. ROC analysis assessed diagnostic performance, while heatmap and PCA were used to examine biomarker relationships and clustering. Patients with thalassemia had significantly elevated serum levels of GFAP and RANKL. ROC curve analysis demonstrated excellent diagnostic accuracy for both markers: GFAP yielded an AUC of 100%, while RANKL showed an AUC of 99%. A strong positive correlation between the two biomarkers was observed in patients. PCA further confirmed a distinct biochemical profile in thalassemia, with both markers contributing prominently to group separation. The findings suggest that GFAP and RANKL may serve as promising biomarkers for detecting neurological and bone-related alterations in thalassemia. Their diagnostic potential supports further investigation into their role in disease mo n itoring and management.